Designs for sensory-motor tests and other psychological apparatus - De Wet, Daniel Richard (Department of Psychology, 2016)
The design and construction of equipment for both basic psychological research and applied purposes in occupational selection and guidance, ergonomics, and training, is an important area that has hitherto received comparatively little recognition. Apparatus is often taken very much for granted as useful furniture affording some passive assistance in the study of behaviour, but nevertheless remaining something extraneous, that belongs more fittingly in the realm of mechanics. Actually, the design and construction of testing equipment, no less than its application, is very intimately related to the measurement of psychological functions. Behavioural results can be no more sound than the instruments and techniques employed in deriving them. This dissertation attempts to make some contributions of a twofold kind: Technological, comprising detailed illustrated descriptions of some original apparatus designs by the writer, and Behavioural, comprising accounts of research findings obtained with these, mainly on air-pilot candidates for the South African Air Force, and African industrial personnel.